Differences in Health-Related Quality of Life and Its Associated Factors Among Older Adults in Urban and Rural Areas - Zhang J; Xiao S; Shi L; Xue Y; Zheng X; Dong F; Xue B; Zhang C (Dove Medical Press, 2022)
Jiachi Zhang,1 Shujuan Xiao,1,2 Lei Shi,1 Yaqing Xue,1,2 Xiao Zheng,1,2 Fang Dong,1 Benli Xue,1 Chichen Zhang1,3,4 1School of Health Management, Southern Medical University, Guangzhou, People's Republic of China; 2School of Public Health, Southern Medical University, Guangzhou, People's Republic of China; 3Department of Health Management, Nanfang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 4Institute of Health Management, Southern Medical University, Guangzhou, People's Republic of ChinaCorrespondence: Chichen Zhang, School of Health Management, Southern Medical University, No. 1023 Shatai South Road, Baiyun District, Guangzhou, 510515, People's Republic of China, Tel +86-20-61648756, Email zhangchichen@sina.comPurpose: Urban-rural health disparity is one of the most prominent challenges in China today. The goal of this study is to find differences in health-related quality of life (HRQoL) and its associated factors among older people in urban and rural areas.Methods: A multi-stage stratified sampling method was conducted in Shanxi Province, with a total of 3250 older adults participated in this cross-sectional survey. HRQoL was assessed using the Chinese version of the EQ-5D-5L. Tobit regression models were employed to identify associated factors for HRQoL.Results: The mean EQ-5D utility score of the total sample was 0.87± 0.23, with a statistically significant difference observed between urban (0.89 ± 0.22) and rural areas (0.86 ± 0.23). Obesity (Coe=− 0.10, p=0.021) and nutrition awareness (Coe=− 0.14, p=0.009) were two unique associated factors to rural older adults' HRQoL. While, age (Urban: Coe=0.13, p=0.001; Rural: Coe=− 0.019, p< 0.001), socioeconomic status (Urban: Coe=0.13, p< 0.001; Rural: Coe=0.14, p< 0.001), number of chronic non-communicable diseases (Urban: Coe=− 0.20, p< 0.001; Rural: Coe=− 0.15, p< 0.001), sleep quality (Urban: Coe=− 0.22, p< 0.001; Rural: Coe=0.15, p< 0.001) and daytime sleepiness (Urban: Coe=− 0.13, p< 0.001; Rural: Coe=− 0.13, p< 0.001) were found to be associated with HRQoL regardless of the residential area.Conclusion: This study suggested that rural older adults are facing HRQoL disadvantages compared to those in urban area. Accordingly, more attention should be devoted to rural older adults' HRQoL, particularly to the unique factors like body weight and nutrition awareness. Targeted policies and interventions should be implemented to improve HRQoL and bridge the urban-rural HRQoL gap.Keywords: health-related quality of life, HRQoL, older adults, urban and rural, health management